Stable Sr isotope (88Sr/86Sr) fractionation in calcite precious corals - Yoshimura, Toshihiro; Wakaki, Shigeyuki; Iwasaki, Nozomu; Ishikawa, Tsuyoshi; Ohkouchi, Naohiko (Frontiers in Marine Science, 2022)
Stable isotope ratios of Sr (88Sr/86Sr) are a novel indicator for identifying terrestrial and oceanic Sr cycling and biological processes. Here we evaluate the temperature dependence of stable Sr isotope ratios (δ88Sr) in the calcite skeletons of precious corals, known as octocorals. High-precision Sr isotope measurements by double spike thermal ionization mass spectrometry were applied to different precious corals (Corallium japonicum, Pleurocorallium elatius, P. konojoi, Corallium sp., Keratoisis sp., and Coralliidae sp.) collected from water depths of 30–1500 m in the Pacific Ocean, corresponding to annual mean water temperatures of 2.5 to 19.5°C. The precious corals showed mean δ88Sr values of 0.101 ± 0.023‰. The magnitude of Sr isotope fractionation between the skeleton and ambient seawater (Δ88Sr) is −0.291 and is about −0.1‰ lower than the value predicted from the precipitation of inorganic calcite. This fractionation is not affected by changes in skeletal Sr/Ca ratio and associated biological effects on δ88Sr are negligible. δ88Sr of precious coral skeleton is an excellent recorder of ambient seawater.